Citizens' Educational Rights and Obligations in the Implementation of Statehood - Dwi Novalia; Yuan Indira Puspitasari; Devi Yuliawati (Annujum: Journal of Humaniora and Law, 2026)
This article discusses how the Constitution of the Republic of Indonesia guarantees education as a fundamental right for every citizen, particularly through Article 31, which guarantees universal access to education. Furthermore, this article analyzes the fourth paragraph of the Preamble to the Constitution. This study examines recent literature from 2020 to 2025. The review indicates that education is not yet fully optimized due to the limited number of government education programs and resource distribution. Therefore, to improve the effectiveness of education, it is necessary to continuously update the education model, enrich learning materials, and ensure equal access across all educational institutions.